Phenytoin: Clinical Use, Pharmacokinetics, Pharmacodynamics, Toxicology, Side Effects, Contraindication, and Drug Interactions - Gavriel Fauzan Faturachman; Lolita Tiara Sari; Naura Artanti; Shakira Shakira; Tsabita Nafla Zalikha (Universitas Negeri Semarang, 2022)
Phenytoin is an antiepileptic drug derived from an organic compound called hydantoin. Phenytoin is an antiepileptic drug primarily used to treat seizures in people with epilepsy. Phenytoin works by targeting and blocking voltage-gated sodium channels in the nervous system, which helps reduce abnormal electrical activity in the brain that leads to seizures. Phenytoin can also be used to treat trigeminal neuralgia and ventricular tachycardia. Absorption of phenytoin depends on the mode of administration either peroral or parenteral. The distribution of phenytoin is affected by plasma protein binding. Phenytoin is metabolized primarily by liver enzymes, especially the cytochrome P450 enzyme system. Phenytoin excretion is influenced by the pH in the urine. Side effects of phenytoin use that can occur are sedation, hallucinations, fever, sedation, confusion, hallucinations, peripheral neuropathy, stevens-johnson syndrome, cardiovascular collapse, hypotension, purple glove syndrome, nystagmus, ataxia, nausea, coma, seizures, vomiting, hyperactivity, lethargy, fetal hydantoin syndrome (FHS), and megaloblastic anemia. Contraindications to the use of phenytoin are in someone with hypersensitivity to phenytoin or other hyndatoin, pregnant women, and lactating women. Oral phenytoin overdose causes neurotoxicity and parenteral phenytoin overdose causes cardiovascular toxicity. There is no specific antidote for phenytoin toxicity and the usual treatment is supportive care. There are various drugs that can interact with phenytoin to decrease or increase phenytoin levels.